Newspaper infographics as an informative genre in the media - García González, Daniel (Historia y Comunicación Social, 2014)
From their eclosion during the 1990s until now, statistical graphics, maps, diagrams and many other newspaper infographics have became a new informative genre in the media all around the world. This paper –which is strictly oriented to social media infographics– analyzes those minimal units in which graphics can be divided and explores a possible classification for methdological purposes. Differences between static infographics –those designed to read be in printed media– and interactive ones are considered too.
Keywords: Infographics; graphics; genres; media; journalism.